Low muscle mass, low muscle function, and sarcopenia in the urban and rural elderly - Sung Woo Moon; Kwang-Joon Kim; Han Sung Lee; Young Mi Yun; Jong-Eun Kim; You Jin Chun; Chang Oh Kim (Scientific Reports, 2022)
Abstract Health outcomes of the elderly vary between rural and urban areas. Sarcopenia is diagnosed as loss of muscle strength or impaired physical performance, namely “low muscle function” and low muscle mass. Outcomes of low muscle mass and low muscle function are not equal. This study aimed to investigate the prevalence of low muscle mass, low muscle function, and sarcopenia in rural and urban populations and to determine whether regional differences were associated with each of these components. Participants aged ≥ 69 years (n = 2354) were recruited from three urban districts and one rural district in Korea. Low muscle mass was defined by appendicular lean mass using bioelectrical impedance analysis. Low muscle function was defined by handgrip strength and 5-chair stand test. Sarcopenia was defined as low muscle mass plus low muscle function. The prevalence of low muscle function (53.7% vs. 72.8%), and sarcopenia (16.3% vs. 24.4%) were higher in the rural elderly population. Rural residence was associated with low muscle function (OR 1.63; 95% CI 1.13–2.37, P = 0.009), but not with low muscle mass (OR 0.58; 95% CI 0.22–1.54, P = 0.271) or with sarcopenia (OR 1.13; 95% CI 0.63–2.00, P = 0.683). Interventions to detect and improve low muscle function in rural elderly population are needed.